Theoretical Study of the Reaction Formalhydrazone with Singlet Oxygen. Fragmentation of the C=N Bond, Ene Reaction and Other Processes1. (2nd December 2013) - Rudshteyn, Benjamin; Castillo, Álvaro; Ghogare, Ashwini A.; Liebman, Joel F.; Greer, Alexander
Abstract Photobiologic and synthetic versatility of hydrazones has not yet been established with 1O2 as a route to commonly encountered nitrosamines. Thus, to determine whether the "parent" reaction of formalhydrazone and 1O2 leads to facile C=N bond cleavage and resulting nitrosamine formation, we have carried out CCSD(T)//DFT calculations and analyzed the energetics of the oxidation pathways. A [2 + 2] pathway occurs via diradicals and formation of 3‐amino‐1, 2, 3‐dioxazetidine in a 16 kcal/mol−1 process. Reversible addition or physical quenching of 1O2 occurs either on the formalhydrazone carbon for triplet diradicals at 2–3 kcal mol−1, or on the nitrogen (N(3)) atom forming zwitterions at ~15 kcal/mol−1, although the quenching channel by charge‐transfer interaction was not computed. The computations also predict a facile conversion of formalhydrazone and 1O2 to hydroperoxymethyl diazene in a low‐barrier 'ene' process, but no 2‐amino‐oxaziridine‐O‐oxide (perepoxide‐like) intermediate was found. A Benson‐like analysis (group increment calculations) on the closed‐shell species are in accord with the quantum chemical results.